Peran PAK Keluarga Dalam Menghadapi Perilaku Menyimpang Remaja di Jemaat GMIM Yudea Paal Dua - Margarith Loho; Grace Birahim (Peneliti.net, 2020)
This research is a study that uses qualitative methods and aims to find out how the role of family Christian Religious Education in dealing with the deviant behavior of adolescents in the GMIM Judea Paal Dua Congregation. Data collection techniques are carried out through observation, interviews and documentation studies. The results showed that: (1) The implementation of Christian Religious Education in the family has not been carried out properly. (2) The cause of the occurrence of deviant behavior of adolescents lies in the parents and the social environment. (3) Actions that will be taken by the family in the face of adolescent deviant behavior, namely by embracing the adolescent and building good communication and providing direction for the adolescent. From the results of the study, it is recommended for families to be more active in the implementation of family PAK so that the attitudes and character of adolescents can be formed into good individuals, and adolescents can practice Christian values in their lives every day.